Distributed Autonomous Robotic Systems The 12th International Symposium - Chong, Nak-Young; Cho, Young-Jo (Springer Tracts in Advanced Robotics,, 2016)
This volume of proceedings includes 32 original contributions presented at the 12th International Symposium on Distributed Autonomous Robotic Systems (DARS 2014), held in November 2014. The selected papers in this volume are authored by leading researchers from Asia, Europe, and the Americas, thereby providing a broad coverage and perspective of the state-of-the-art technologies, algorithms, system architectures, and applications in distributed robotic systems. .